Species richness and diversity along edaphic and climatic gradients in Amazonia - Hanna Tuomisto; Gabriela Zuquim; Glenda Cárdenas (My University, 2022)
The number of species is known to decrease from the humid tropics towards drier and colder climates, but how species richness varies along environmental and spatial gradients within the tropical rain forests is not clear. We inventoried 214 transects of 0.25 ha to document species diversity patterns in an example plant group (ferns and lycophytes) across non-inundated rain forests of western and central Amazonia, and assessed how well these conformed with proposed hypotheses about species richness. The observed number of species varied between 6 and 71 per transect. The effective number of species (emphasising the degree of unevenness in species abundances) varied between 1.02 and 8.60, and diversity profiles revealed considerable differences among transects in community structure. Although the density of individuals varied over almost two orders of magnitude, species diversity was better explained by other variables. In particular, within-transect species diversity increased substantially with increasing soil cation concentration. It also increased with soil aluminium concentration, heterogeneity in soil chemistry, annual rainfall and dry season rainfall, and was higher in western than in central Amazonia. Multiple regression models explained up to 70% of the variance in species diversity, but the relationships between species diversity and the environmental gradients became progressively weaker as species abundances were given more weight in the calculation of diversity. Our results conformed to the proposal that site productivity promotes species diversity. This seemed to arise from larger species pools on more fertile soils and in wetter climates, even when it could be expected that the older and more widespread infertile soils would have provided more opportunities for speciation. © 2014 The Authors.